Real-World Use of Carvedilol in Children With Dilated Cardiomyopathy: Long-Term Effect on Survival and Ventricular Function - Adorisio, Rachele; Cantarutti, Nicoletta; Ciabattini, Marco; Amodeo, Antonio; Drago, Fabrizio (Frontiers in Pediatrics, 2022)
Background Carvedilol is recommended for chronic heart failure (HF) treatment in children. However, the ideal dosage and administration are not standardized, and data on its long-term effects are lacking. This study aimed to assess the effect of a high dosage regimen of carvedilol on cardiac outcomes in children with HF. Methods We conducted a retrospective cohort study including all children with HF and dilated cardiomyopathy. We analyzed medical records before starting treatment, at 1 and 3 years after reaching the maximum therapeutic dosage. All data were compared with a historical control group. Kaplan–Meier analysis and Cox proportional hazard regression have been used to evaluate the effect of high dosage carvedilol therapy. The main outcome was a composite of all-cause mortality and heart transplant. Results One hundred thirty-five were included in the study and 65 treated with a high dosage of carvedilol regimen (up to 1 mg/kg/day). Heart rate reduction (mean reduction 30%, p < 0.0001) and ejection fraction improvement (32 ± 9.4 vs. 45. ± 10.1%, p < 0.0001) were statistically significant in those. Long-term survival and freedom from heart transplant were significantly improved in those treated with high dosage carvedilol therapy (p = 0.00001). Conclusions Treatment with the high dosage of carvedilol, in addition to standard HF therapy, significantly improves ventricular function and survival in children with dilated cardiomyopathy and chronic HF.